The Design and Implementation of Reading Aid Tools Based on Raspberry Pi for Blind EFL Students - La Ode Rusadi; Nur Mutmainna Halim; Muh Taufik; Dahniar Dahniar (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Because there is a dearth of accessible reading material, especially braille printed books, this blind reading aid was developed for EFL students. No longer will a blind learner have to rely on braille-printed books to learn and grow. This technology enables visually impaired EFL students to access the same literary works as their sighted peers. This study employs a qualitative approach to experimentation, with data gathered through observation, interviews, and a review of existing literature. This system planning is described using a flowchart and block diagram. The Blackbox testing approach was employed to conduct the tests in this research. The Raspberry Pi was used as the microcontroller, and the Push Button on the Raspberry Pi Camera was used to initiate the graphical capture and subsequent image file processing by Optical Character Recognition (OCR) and Text-to-Speech (TTS). This procedure yields an mp3 file that can be played through loudspeakers or speakers, allowing blind people to